2013
DOI: 10.1007/s11262-013-0932-0
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a key residue for hyperfusogenic phenotype in human parainfluenza virus type 2 (hPIV-2) fusion glycoprotein

Abstract: Human parainfluenza viruses (hPIV) are pathogens responsible for upper and lower respiratory tract infections. We previously described clinical variant strains of hPIV-2 that display unusual large syncytial cytopathic effects. Their molecular characterization revealed a recurrent conserved specific amino acid substitution: A96T in the F2 subunit of the fusion glycoprotein F. The objective of this study was to investigate the contribution of this A96T substitution to the specific hyperfusogenic properties of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Le Bayon et al [] reported that amino acid substitution A96T in the F2 subunit strongly alters fusogenic properties of the fusion protein. Here, it is shown (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Le Bayon et al [] reported that amino acid substitution A96T in the F2 subunit strongly alters fusogenic properties of the fusion protein. Here, it is shown (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%